A surface plasmon resonance temperature sensor using TiO2 nanoparticles on hetero-core fiber optic structure with Au thin film. (1st May 2022) - Yuhashi, Koji; Ida, Junichi; Kubodera, Shoichi; Watanabe, Kazuhiro; Nishiyama, Michiko
Abstract: A surface plasmon resonance (SPR)-based temperature sensor was developed based on hetero-core structured fiber optics with multilayer films of titanium dioxide (TiO2 ) nanoparticles (NPs) and poly-L-lysine (PLL) formed by electrostatic interaction as a simple wet process on gold (Au) film onto a cylindrical cladding surface. We experimentally observed that the resonant wavelength shifted 135.6 nm toward a shorter wavelength for a temperature change from 100 °C to 300 °C. In light intensity-based measurement, the sensitivity of the transmitted loss change was 1.8 × 10 −2 dB °C −1 at a wavelength of 700 nm when 19 layers of TiO2 NPs and PLL was annealed onto a 40 nm thick Au film, which improved by over 12 times higher sensitivity than in the conventional radiofrequency (RF) sputtering fabrication method. The proposed sensor successfully detected temperature changes with high sensitivity and linearity as well as simplified the fabrication process compared with the conventional RF sputtering fabrication method.